Personal agency and borderline personality disorder: a longitudinal study of outcomes - Talia Hashworth; Samantha Reis; Michelle Townsend; Jessica O.’Garr; Brin F.S. Grenyer (BMC Psychiatry, 2022)
Abstract Background Low personal agency is the concept of attributing successes and failures to external factors rather than personal characteristics. Previous research supported links between low personal agency and symptoms of borderline personality disorder (BPD). The present research followed patients in an outpatient dialectical behavioural therapy (DBT) group from intake to 12 months follow up to examine the impact of personal agency on outcome. Methods Patients (N = 57, age 18–72, 91.5% female) were assessed at intake, after three months of DBT treatment, and 12 months follow up on measures of symptoms and personal agency. Three separate measures were used to assess treatment outcomes: the BPD Checklist, the Personality Inventory for DSM-5 (PID-5), and the Mental Health Inventory (MHI-5). Results Mixed model analyses found BPD symptoms significantly reduced as a result of DBT treatment and were maintained at follow-up. However, 47% of participants continued to meet BPD criteria 12 months later, despite treatment. Regression analyses indicated that low personal agency at intake was associated with higher BPD symptom severity at post-treatment and 12 month follow up. In addition, low personal agency at intake was associated with greater levels of negative affectivity at post-treatment. Personal agency did not relate to levels of depression and anxiety. Conclusions Despite the reductions in BPD symptomology, personal agency did not significantly change over time. Those with lower agency at intake continued to do more poorly at follow up. We speculate that poor outcomes may be contributed to by patients' lack of engagement in recovery due to poor agency and an external locus of control. As such, therapeutic approaches, like DBT, may require additional strategies to appropriately target low personal agency. Further research is needed to understand if other treatment protocols may facilitate positive change in personal agency.